Persepsi Mahasiswa Tentang Pemanfaatan Layanan Kesehatan (Studi pada Mahasiswa Fakultas Kesehatan Masyarakat, Universitas Nusa Cendana Angkatan 2020-2021) - Jery Y. Buitlena; Tadeus A.L. Regaletha; Dominirsep O. Dodo (Yayasan Literasi Sains Indonesia, 2022)
Utilization of health services is an important aspect in the development of health status. the use of health services at the national level and in NTT has decreased since 2019-2021, people prefer to self-medicate rather than use health services. based on research on FKM students, utilization of health services is still low even though the problems experienced interfere with activities. This study aims to describe the use of health services by students of the Faculty of Public Health, Nusa Cendana University Class of 2020-2021, based on gender and student perceptions. This research is a descriptive research with survey design method. Samples were selected using the proportionate technique stratified random sampling and sampling was done by simple random sampling technique. Results The research shows that 84.6% of respondents who perceive vulnerable, are male, 81.4% of respondents who have a serious perception, are female, 61% of respondents who perceive useful are female, 62.7% of respondents who perceived inhibited, are female, 78% of respondents who perceive capable, are female, 76.3% of respondents who feel compelled, are female. 71.8% respondents perceived vulnerable, 76.5% respondents perceived serious, 56.5 respondents perceived useful, 60% respondents perceived inhibited, 71.8% respondents perceived capable, 69.4 respondents perceived encouraged. Thus it can be concluded that the majority of respondents have a good perception of the use of health services.